PROBLEMS AND CLASSIFICATION OF FORMER MILITARY AREAS - Svirezhev C.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2014)
Integration of the Russian Federation in the international community, to find the most effective ways to implement the military and land reforms require a comprehensive study. The paper identifies the main problems that hinder the effective implementation of the reform of the conversion, the ways of their solutions, including use of the experience of the advanced countries of the European Union. Identified military objects to be conversion, shown combining them into groups according to various criteria. Proposed a typology of ex-military territories. Notes the role of the organization of effective land use conversion in the areas of land use planning, identifies the main documents required for the implementation of planned activities. The problems of land use planning conversion ex-military territories.